Associated links among mtDNA glycation, oxidative stress and colony sectorization in Metarhizium anisopliae - Li, Lin; Pischetsrieder, Monika; St. Leger, Raymond J.; Wang, Chengshu (Fungal Genetics and Biology, 2008)
Mycelial colonies of filamentous fungi often deteriorate when maintained on artificial media, and this can take the form of sterile sectors. We previously established that sectorization by the entomopathogenic fungus Metarhizium anisopliae correlates with intracellular accumulation of reactive oxygen species (ROS). In this study we demonstrate that: (1) H2O2 increases rates of sectorization; (2) a stable strain of M. anisopliae eliminates intracellular ROS more rapidly than an unstable strain; (3) mitochondrial DNA from sectors undergoes a non-enzymatic glycation of deoxyguanosine that is not shown by genomic DNA; (4) the membrane potential of mitochondria in sector cells is decreased in comparison to wild type cells indicating loss of function; (5) DNA glycation changes the properties of DNA and (6) treating wild type mycelia with H2O2 reproduced the glycation pattern shown in sectors. H2O2 also reproduced the morphological changes in mitochondria and lipid droplets that occur in sector cells. Fungal sectorization thus displays aging related developmental impairments resulting from oxidative stress, suggesting a new research direction for studies on fungal colony deterioration. Mitochondrial DNA has a very high AT bias. We speculate that reducing the consequences of glycation could provide an adaptive reason for this. © 2008 Elsevier Inc.
UnivIS-Import:2015-03-09:Pub.2008.nat.dchph.llmch.associ
Keywords: Lipid droplets; Metarhizium anisopliae; mtDNA glycation; Oxidative stress; Sectorization